Stories for Tolerance (2) (Journal of Parents and Teachers, 2025)
The article is about the diversity in society and how we must all live together in the best possible way. For this reason, a series of books has been selected to address these aspects. Each book includes a summary, recommended ages, publishers, and what can be worked on with them.
Keywords: diversity; society; books; live